2019
DOI: 10.1029/2018gl080839
|View full text |Cite
|
Sign up to set email alerts
|

Mars Science Laboratory Observations of the 2018/Mars Year 34 Global Dust Storm

Abstract: Mars Science Laboratory Curiosity rover observations of the 2018/Mars year 34 global/planet‐encircling dust storm represent the first in situ measurements of a global dust storm with dedicated meteorological sensors since the Viking Landers. The Mars Science Laboratory team planned and executed a science campaign lasting approximately 100 Martian sols to study the storm involving an enhanced cadence of environmental monitoring using the rover's meteorological sensors, cameras, and spectrometers. Mast Camera 88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
185
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 156 publications
(206 citation statements)
references
References 54 publications
20
185
0
Order By: Relevance
“…After the early growth phase a hiatus in dust expansion was observed that lasted for about a week, after which dust expansion accelerated again. The storm became planet encircling by 17 June 2018 ( L s = 194.9°), which coincides with a peak in optical depth of 8.5 measured from the surface by the Curiosity rover (Guzewich et al, ). The GDE reached its mature phase around 23 June 2018 ( L s = 197.9°) (Kass et al, ).…”
Section: Mcs Observations Of the My34 Gdesupporting
confidence: 77%
“…After the early growth phase a hiatus in dust expansion was observed that lasted for about a week, after which dust expansion accelerated again. The storm became planet encircling by 17 June 2018 ( L s = 194.9°), which coincides with a peak in optical depth of 8.5 measured from the surface by the Curiosity rover (Guzewich et al, ). The GDE reached its mature phase around 23 June 2018 ( L s = 197.9°) (Kass et al, ).…”
Section: Mcs Observations Of the My34 Gdesupporting
confidence: 77%
“…However, the strong decrease in the visibility of the surface albedo features was evident throughout the month of June, when all longitudes were covered by the dust as shown in Figure S2. As reported by Guzewich et al (), the eastward progression of the GDS produced a first increase in dust opacity at the Curiosity location (4.6°S, 222.6°W) on 9‐10 June reaching its peak in opacity in 18 June. On 18 June, we see that the dust had covered the Tharsis Mons area (~15°N, 140°W), and most of the surface albedo features of this region and surrounding areas were unrecognizable on June 27.…”
Section: Onset and Initial Expansion Of The Global Dust Stormsupporting
confidence: 72%
“…Non‐detections are localized in time and places: 45% of our non‐detections are located at the onset of the GDS ( 193Ls198, five observations), and the other 55% are located during the GDS ( 219Ls231, six observations) but correspond to low haze top altitude beyond the northern limit of the GDS (see detailed discussion in section ). Second, we observe the presence of two distinct types of vertical profiles that correspond to the two periods separated by the sudden onset of the GDS at Ls195–200 (Guzewich et al, ). Two main cloud characteristics differ between these two periods: the vertical extent and the water ice cloud opacity.…”
Section: Resultsmentioning
confidence: 65%